Association of inflammatory markers with clinical outcome in COVID-19 patients during the second wave in 100 bedded dedicated COVID MCH Hospital, Raigarh, Chhattisgarh State - Pankaj Madhukar Luka; Ved Prakash Gilley; Anmol Madhur Minz; Harish Kumar; Manoj Kumar Minj (Asian Journal of Medical Sciences, 2024)
Background: A novel coronavirus (severe acute respiratory syndrome coronavirus 2 [SARS-CoV-2]) was the causative agent of coronavirus disease 2019 (COVID-19) pandemic 2019. SARS-CoV-2 affects respiratory tract and damages the tissue resulting in generation of inflammatory cells such as cytokines and chemokines such as IFN that damage the lung alveoli, causing severe acute respiratory syndrome.